Impact of the Eduball method on cognitive creativity, motor creativity, and motor fitness during physical education classes in 8- to 9-year-old children - Khorkova, Maryna; Bojkowski, Łukasz; Korcz, Agata; Krzysztoszek, Jana; Łopatka, Marlena; Adamczak, Dagny; Bronikowski, Michał (Frontiers in Public Health, 2025)
IntroductionCreativity is increasingly recognized as a crucial skill across various fields. Although schools are placing more emphasis on fostering creativity, physical education (PE) often remains overlooked. The Eduball method, which combines physical activity with cognitive challenges using educational balls, presents a promising strategy for enhancing both cognitive and motor creativity in children. This study aimed to assess the effectiveness of an Eduball-based PE program in supporting creativity and motor fitness in early school-aged children.MethodsThe study involved 173 primary school children (48% girls) aged 8–9 years. Cognitive creativity was assessed using the Test for Creative Thinking–Drawing Production (TCT-DP). Motor creativity (fluency, originality, imagination) was evaluated using the “Thinking Creatively in Action and Movement” (TCAM) test. Motor fitness was assessed using selected Eurofit battery tests: a 20-meter Shuttle Run to evaluate cardiorespiratory endurance, and a 10 × 5-meter Shuttle Run (SHR) to assess speed and agility. The Piórkowski apparatus (AP) test measured hand-eye coordination, reaction time, and precision of movements. The eight-week intervention used the Eduball method during PE classes in two experimental groups: Experimental Group 1 (EG1) had one Eduball session per week; Experimental Group 2 (EG2) had two. The control group (CG) participated only in traditional PE classes. Pre- and post-tests were analyzed using one-way ANOVA on ranks and the Wilcoxon signed-rank test.ResultsAt the pre-test there were no significant differences between groups in any measured parameter. However, statistically significant differences were observed in the post-test for the TCT-DP scores, motor imagination (TCAM), and eye-hand coordination in AP test, all favoring EG2. Within-group comparisons showed significant improvements in all motor fitness parameters, as well as in TCAM fluency and imagination across all groups. However, no significant change in TCT-DP or TCAM originality was observed in the experimental groups. The control group showed a significant decline in these two parameters.ConclusionThe Eduball method significantly supported selected aspects of creativity and motor fitness among 8–9-year-old children. These findings highlight the method’s potential as an effective pedagogical tool for fostering creativity development through physical education in school settings.